FUNCTIONING OF FINANCIAL AND CAPITAL MARKETS IN MODERN CONDITIONS - Stošić Mihajlović, Ljiljana (Journal of process management and new technologies, 2016)
Financial markets are the lifeblood of the global economy where changes in one part of the world quickly and violently, like waves, spread and affect every country, company and individual. This is most clearly manifested in the great world economic crisis that began precisely on the US financial market, that is where the market is most developed, and extended to all other countries. Financial markets in the modern world are associated with the other segments of the world economy. To understand the phenomenon and fluctuations based on this exhibit, today more than ever necessary to monitor the total change, not only in in economy but also in all other segments of society. The complexity of the mechanisms of financial markets, the large number of participants, the importance of regulation and supervision, but high profits and high risks, so that the understanding of financial markets today are more complex than ever before.